Effect of the Addition of Human Milk Fortifier to Breast Milk on the Early Recovery of Infants After Congenital Cardiac Surgery - Yu, Xian-Rong; Xie, Wen-Peng; Liu, Jian-Feng; Wang, Li-Wen; Cao, Hua; Chen, Qiang (Frontiers in Pediatrics, 2021)
Objective: This article studied the effect of breast milk supplemented with human milk fortifier (HMF) on the early recovery of infants after congenital cardiac surgery. Methods: Infants undergoing congenital cardiac surgery were randomly divided into an intervention group (n=27) and a control group (n=27). Infants in the intervention group received HMF, and those in the control group were exclusively breastfed. The nutritional indicators at discharge, the postoperative recovery status, and nutritional-related complications were recorded. Results: Compared with the control group at the time of discharge, the weight and albumin and prealbumin levels of the intervention group were significantly increased (P<0.05). The length of hospital stay of the intervention group was significantly reduced compared with that of the control group (P<0.05). Although the length of ICU stay for the intervention group was shorter than that of the control group, the difference was not significant (P>0.05). No significant difference in the incidence of postoperative nutrition-related complications was noted between the two groups (P>0.05). Conclusion: Compared with breastfeeding alone, with HMF can improve postoperative weight gains, reduce the length of stay, and promote infants’ early recovery after congenital cardiac surgery.